Some Deafness-Causing Mutations Can Be Silenced with the Appropriate Gene Partner - Edward Wilcox; Saima Riazuddin; Sheikh Riazuddin (The Scientific World Journal)
Inheritance of a deafness-causing genotype does not necessarily mean that a person will have profound hearing loss. The presence of a modifying gene can change the effect of the deafness genotype. As an example, mutations found commonly among the deaf are at times found among their normal hearing relatives [1]. The implication is that there are genes or gene products whose interactions allow the normal physiological function of the inner ear despite a mutation that would normally disrupt the process. Deafness is not the first disorder in which modifiers can change the expected outcome, nor will it be the last, but it is very unusual for the outcome to be so dramatically changed.